تعليم القرآن في معهد الدراسات الإسلامية قه دانغ ديان في الصين : دراسة وصفية تقويمية (1992-1995م) /‏ - لي، كيانغ موي
In early times, Islam entered China as a result of Muslims practicing the Prophet's (Peace be upon him) saying, “Convey from me even a verse.” The Chinese, who were deeply influenced by those Muslims, converted into Islam and obeyed the Islamic Law. Muslims have played a significant role in the preaching of Islam and Islamic culture, while stoically facing the challenges of different historical periods in China. However, they still build mosques and turn them into education centers to preserve religion and identity. Thus arose the new nation (Hui), which represents Muslims of Arab origin and new Muslim Chinese generations who contributed to the development of China's civilization and society. The researcher chose the Institute of Islamic Studies (Ge Dang Dian) as a model in the dissemination of Islamic education, curriculum and courses adopted, and the teaching methods used during the period 1992 AD-1995 AD (1402 AH-1405 AH) and evaluated the curricula of the institute and its education performance, especially after the Cultural Revolution which was intended to dissolve the Islamic identity. As the subject was studied for the first time in Chinese and Arabic languages, this research used scientific methods such as historical, descriptive, field and analytical methods. Through this study, the results achieved the following: disclosure about the role of immigrants from Ethiopia in spreading Islam in China, proving the role of nationalism (Hui) in the propagation of Islam, and the establishment of mosque's schools and Islamic institutes, disclosure of the role of scholars (Hui) in education and their sacrifice for the continuation of schools and colleges in carrying out scientific and educational purposes while devising ways and means available to keep the identity of Islam and the Muslims and explaining the role of the Institute of Islamic Studies (Ge Dang Dian) enhances Islamic identity and scientific development in the Muslim community in particular and the Chinese community in general.